Miki Falls. Book 4, Winter - Crilley, Mark (HarperTeen, 2008)
Miki and Hiro travel through the icy north, followed closely by Akuzu, who is determined to tear the young couple apart. Miki does everything in her power to beat the odds and make sure that she and Hiro remain together.